(untitled) - Rosenwald, Peter J.; by Peter J. Rosenwald ([Chicago, Ill.],New York, NY)
Businesses are increasingly concerned about measurability and accountability - particularly in the area of marketing. Executives and managers are searching for reliable methods to ensure that they are getting more out of their marketing efforts, as well as for ways to continue successful operations. If you could differentiate between your best customers, your marginal customers and your worst customers, would you spend your marketing monies the way you do today? If youÂ're like most marketers, you would not. Then get yourself a copy of Accountable Marketing, and together with its CD of 35 Interactive Templates, discover how to concentrate your marketing expenditures for greater profits
Includes bibliographical references and index
Keywords: Marketing; Marketing; Marketing